Boundary element method for two-dimensional steady heat conduction in solids - Lum, Bing Heng (Nanyang Technological University, 2022)
Boundary Element Method is a numerical method for solving partial differential equations. Some problems in engineering that could be solved using such a method include the heat conduction through a material. This report explores using the boundary element method to solve steady state heat conduction problems through a two-dimensional solid. Boundary Element Method is implemented and compared against the Fourier Series solution of the temperature of the solid to determine the validity of the Boundary Element Method solution.